2021
DOI: 10.3390/microorganisms9061329
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Sorghum Genotypes Tolerant and Sensitive to Nitrogen Stress Select Distinct Root Endosphere and Rhizosphere Bacterial Communities

Abstract: The belowground microbiomes have many beneficial functions that assist plant growth, including nutrient cycling, acquisition and transport, as well as alleviation of stresses caused by nutrient limitations such as nitrogen (N). Here we analyzed the root endosphere, rhizosphere and soil bacterial communities of seven sweet sorghum genotypes differing in sensitivity to N-stress. Sorghum genotypes were grown in fields with no (low-N) or sufficient (high-N) N. The dry shoot weight ratio (low-N/high-N) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
2
8
0
Order By: Relevance
“…These results were corroborated by our analysis of amplicon sequences from 2016, as well as metagenomes assembled from both 2016 and 2017 samples that showed a significant increase in nitrogen-fixing genes under low nitrogen (Supplementary Figure 6). Similar patterns have been identified in other studies of the sorghum rhizosphere (Yu et al 2011, Hara et al 2019, Lopes et al 2021, Wu et al 2021. Interestingly, this nitrogen-fixing guild seems to be preceded by other putatively plantgrowth promoting taxa, such as Massilia and Bacillus (clusters 12 and 17), whose abundances were also higher under low nitrogen.…”
Section: Real Data Analysissupporting
confidence: 85%
“…These results were corroborated by our analysis of amplicon sequences from 2016, as well as metagenomes assembled from both 2016 and 2017 samples that showed a significant increase in nitrogen-fixing genes under low nitrogen (Supplementary Figure 6). Similar patterns have been identified in other studies of the sorghum rhizosphere (Yu et al 2011, Hara et al 2019, Lopes et al 2021, Wu et al 2021. Interestingly, this nitrogen-fixing guild seems to be preceded by other putatively plantgrowth promoting taxa, such as Massilia and Bacillus (clusters 12 and 17), whose abundances were also higher under low nitrogen.…”
Section: Real Data Analysissupporting
confidence: 85%
“…A recent study reported that the genus Streptomyces was enriched in the root endosphere of a nitrogen stress-tolerant sweet sorghum line under low-nitrogen eld growth (Lopes et al, 2021). In this study, not only the genus Streptomyces predominated the bacterial microbiota in the maturing roots of N778, but OTU434 and OTU1304 were also particularly enriched in the maturing root sample of N778 when compared to the control sorghum line TP60 (Table S7).…”
Section: Discussionmentioning
confidence: 49%
“…(Gram-positive) were from the soil. Despite being widely distributed and abundant in the soil and/or rhizosphere of various crops, the genera Chitinophaga (Chung et al, 2012;Li et al, 2014;Chiniquy et al, 2021) and Caulobacter (Gao et al, 2018;Lopes et al, 2021a) are rarely tested for their plant growth-promoting abilities. Compared to these two genera, the genus Terrabacter has also been detected in many plant species, including maize (Dohrmann et al, 2013), sorghum (Lopes et al, 2021a), and napa cabbage (Bhattacharyya et al, 2018), but in very low abundance and is understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being widely distributed and abundant in the soil and/or rhizosphere of various crops, the genera Chitinophaga (Chung et al, 2012;Li et al, 2014;Chiniquy et al, 2021) and Caulobacter (Gao et al, 2018;Lopes et al, 2021a) are rarely tested for their plant growth-promoting abilities. Compared to these two genera, the genus Terrabacter has also been detected in many plant species, including maize (Dohrmann et al, 2013), sorghum (Lopes et al, 2021a), and napa cabbage (Bhattacharyya et al, 2018), but in very low abundance and is understudied. Therefore, we sought to determine whether these bacteria could promote plant growth and their host colonization efficiency with different inoculation methods since they are phylogenetically distinct and exhibit different cell wall structure.…”
Section: Introductionmentioning
confidence: 99%